In company : intermediate student's book with cd-rom - Powell, Mark. (Oxford, England : Macmillan Education, 2009)
The second edition Student's Books contain clearly defined topic and skills-based units, real-world tasks and more case studies, all which are instantly relevant to everyday business life development. The CD-ROM has an interactive glossary and class audio as MP3 downloads.
BSBA
Keywords: English language -- Business English -- Textbooks for foreign speakers; English language -- Business English -- Problems, exercises, etc